Land and society in early colonial Philippines (introduction to the panel). - Churchill, Bernardita Reyes (2010)
There is a great imbalance in Philippine historiography both in subject and period coverage. Much has been written about the initial encounter in the 16th century between the Spanish and the indigenous population in the lowlands/coastal/islands of the archipelago, i.e., the conquest, conversion (Christianization) and resettlement (reduccion), and their immediate consequences for the indigenous communities that came under Spanish rule. New institutions, traditions and social relationships were forming in these communities but there has been no in-depth study of the nature of that society and how Spanish rule transformed (or not) that society. Such a study could inform us of the implications and consequences of change and transformation in Philippine society at that time and to the present.
Keywords: History -- Social aspects; Philippines -- Colonization -- History